Внешнеполитические воззрения антифедералистов в США: эссе 1787-1788 гг. - Дорофеев, Д.В. (Культура народов Причерноморья, 2013)
В статье анализируется проблема внешнеполитических взглядов антифедералистов,
которые писали и публиковали эссе на протяжении 1787-1788 гг. Результаты исследования позволили
установить круг авторов, которые рассматривали внешнеполитические темы, выявить локальную
специфику распространения работ, сравнить взгляды антифедералистов.
Ключевые слова: Генезис внешней политики США, антифедералисты, внешнеполитический механизм,
Конституция 1787 г. У статті аналізується проблема зовнішньополітичних поглядів антифедералістів, які
писали і публікували есе протягом 1787-1788 рр. Результати дослідження дозволили встановити коло
авторів, які розглядали зовнішньополітичні теми, виявити локальну специфіку поширення робіт,
порівняти погляди анти федералістів.
Ключові слова: Генезис зовнішньої політики США, антифедералісти, зовнішньополітичний механізм,
Конституція 1787 p. The central issue is to study the genesis of foreign policy of the U.S.A.
An integral component of the study of the genesis of American foreign policy during the XVIII century is creation
of the foreign policy mechanism according the Constitution of 1787. The purpose of article is study the foreign
policy views of the anti-Federalists in the pamphlets published within the period 1787-1788. Results of the study
let identify authors, who regarded foreign policy topics, detect specific local distribution of works, compare the
anti-Federalist views.
The following findings were obtained.
1. The group of authors 32 anti-Federalist opponents of the ratification of the Constitution was identified.
2. It was specified the geographical specificity of anti-Federalist in the states. The number of authors in
Pennsylvania was 8, New York City – 6, Massachusetts – 5, Virginia – 4, Maryland – 3, Rhode Island – 1
Connecticut – 1 Georgia – 1. The largest number of works – 75% – was spread in Pennsylvania, Massachusetts
and New York. To a lesser extent of essays – 25% – were distributed in Virginia, Maryland, South Carolina,
Rhode Island, Connecticut, Georgia, New Hampshire, Delaware, and New Jersey.
3. Comparative analysis of the anti-Federalist papers showed: first, the lack of unity of the author's position on
the issue of the availability of external sources of threats to the U.S. security, second, the unanimous criticism of
the foreign policy mechanism on the Constitution.
Key words: Genesis of the USA foreign policy, anti-Federalists, foreign policy mechanism, the Constitution of
1787.